Relationship of CD147 kidney expression with various pathologic lesions, biochemical and demographic data in patients with classes III and IV of lupus nephritis - Masoud Amiri; Farima Abedini; Azar Baradaran (Society of Diabetic Nephropathy Prevention, 2018)
Background: Systemic lupus erythematosus (SLE) is a chronic inflammatory disorder that affects the kidney in around 50% of patients Objectives: The aim of this study was to assess CD147 expression with various pathologic lesions, biochemical and demographic data in patients with classes III and IV lupus nephritis. Patients and Methods: These patients with lupus nephritis classes II and IV by renal biopsy and pathology were enrolled in this study. The strength of CD147 staining on tubules, Bowman's capsules, vessels and tuft of glomeruli was expressed as proportion of involvement. Results: In this study, 23 renal biopsies for lupus nephritis of classes III and IV (documented by immunofluorescence and light microscopic studies) were included. No significant difference of CD147 staining between classes was detected (P>0.05). In addition, proportion of proteinuria was not related to CD147 staining in tubules, Bowman's capsules, vessels and tuft of glomeruli in classes III and IV lupus nephritis (P>0.05). There was no significant association of CD147 staining in tubules, Bowman's capsules and vessels with serum creatinine (P>0.05). However, an association between CD147 staining in tuft of glomeruli with serum creatinine was detected (r=0.623, P=0.002). None of chronicity or activity percent of glomerular involvement in two classes of III or IV had a significant association with CD147 staining (P>0.05). Conclusions: The significant association between CD147 staining in glomeruli with serum creatinine in lupus nephritis of classes III and IV revealed that inflammation at this area may have prognostic implication.